2013
DOI: 10.1155/2013/623420
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of 25-Hydroxyvitamin D and Dyslipidemia in Indian Subjects

Abstract: Background. Vitamin D deficiency is widespread throughout the world. Several reports have incriminated vitamin D deficiency as the cause of rickets, osteomalacia, and other chronic diseases. Recent studies have suggested a possible link between deficiency of 25-hydroxyvitamin D and dyslipidemia. Aim. To investigate the association between 25-hydroxyvitamin D deficiency and dyslipidemia in Indian subjects. Methodology. We recruited 150 asymptomatic consecutive subjects from patients' attendees at the Department… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 45 publications
(61 reference statements)
6
53
1
1
Order By: Relevance
“…An Indian population based study concluded this significant association with dyslipidemia after observing a positive correlation with HDL and negative correlation with remaining fractions of lipid profile. 27 Deficiency of vitamin D may initiate the elevation of lipolysis circulating free fatty acids and increase hepatic synthesis of LDL cholesterol. Furthermore, in support of these findings, a study based on premenopausal women concluded even after considering lifestyle factors serum 25(OH) D was negatively associated with TC, TG and LDL-C and positive association with HDL-C. 28 …”
Section: Discussionmentioning
confidence: 99%
“…An Indian population based study concluded this significant association with dyslipidemia after observing a positive correlation with HDL and negative correlation with remaining fractions of lipid profile. 27 Deficiency of vitamin D may initiate the elevation of lipolysis circulating free fatty acids and increase hepatic synthesis of LDL cholesterol. Furthermore, in support of these findings, a study based on premenopausal women concluded even after considering lifestyle factors serum 25(OH) D was negatively associated with TC, TG and LDL-C and positive association with HDL-C. 28 …”
Section: Discussionmentioning
confidence: 99%
“…High serum vitamin D levels are associated with a favorable lipid profile 24 and low serum vitamin D levels have been associated with dyslipidamia including elevated LDL cholesterol and low HDL-C levels in Indian participants. 25 The postulated mechanisms include vitamin D-mediated calcium absorption reducing hepatic triglyceride formation and secretion, regulation of VLDL cholesterol receptor expression, increased peripheral removal of triglycerides and reduction of VLDL cholesterol and triglycerides secondary to reducing insulin resistance. 25 …”
Section: Metabolic Syndromementioning
confidence: 99%
“…It is prevalent in various parts of the world including India with an increased occurrence in high and low latitude countries. 9 In recent years the prevalence of vitamin D deficiency has increased. There is a high prevalence of vitamin D deficiency in pregnant women from nonwestern countries residing in northern Europe, indeed vitamin D deficiency during pregnancy is an ongoing epidemic.…”
Section: Introductionmentioning
confidence: 99%